Cost-minimization analysis of subcutaneous versus intravenous trastuzumab administration in Chilean patients with HER2-positive early breast cancer - Rojas, Luis (PLoS One, 2020)
PURPOSE: Trastuzumab (TZM) improves survival and the risk of recurrence among patients with early-stage HER2+ breast cancer (BC). TZM treatment can be given intravenously (IV-TZM) or subcutaneously (SC-TZM). Although both methods have similar efficacy and safety, they differ in dosage and administration. Previous studies of cost minimization determined that SC-TZM is associated with lower costs than IV-TZM; however, those studies did not include the costs associated with body weight-based dosage and the treatment of adverse drug reactions (ADRs). METHODS/PATIENTS: We performed a model-based cost-minimization analysis. The analysis included direct and indirect medical costs associated with TZM preparation (adjusted by body weight) and administration and also costs due to severe ADRs and non-medical costs that occurred during the total treatment course (18 cycles). We performed a sensitivity analysis to test the robustness of the results across various TZM costs and patient body weights. RESULTS: The overall cost (in USD) of IV-TZM treatment was $83,309.1 per patient compared with $77,067.7 per patient for SC-TZM. Thus, one year of SC-TZM treatment cost $6,241.4 less per patient than one year of IV-TZM treatment. The sensitivity analysis revealed that the results were mainly driven by the price of each TZM vial and body weight. CONCLUSION: SC-TZM is a cost-saving therapy for Chilean patients with early-stage HER2+ BC. Given their similar efficacy and safety, we suggest the use of SC formulations rather than IV formulations. The use of SC-TZM instead of IV-TZM may have a significant economic impact on public/private healthcare systems.